Punishment and Desert - Gregg D. Caruso (Humana.Mente: Journal of Philosophical Studies, 2022)
This paper explores the relationship between punishment and desert and offers two distinct sets of reasons for rejecting the retributive justification of legal punishment — one theoretical and one practical. The first attacks the philosophical foundations of retributivism and argues that it’s unclear that agents have the kind of free will and moral responsibility needed to justify it. I present stronger and weaker versions of this objection and conclude that retributive legal punishment is unjustified and the harms it causes are prima facie seriously wrong. The second objection maintains that even if one were to assume that wrongdoers are deserving of retributive punishment, contra concerns over free will, we should still abandon retributivism since there remain insurmountable practical difficulties that make it impossible to accurately and proportionally distribute legal punishment in accordance with desert. In particular, I present the Misalignment Argument and Poor Epistemic Position Argument and argue that, taken together, they create a powerful new challenge to retributivism called the Retributivist Tracking Dilemma.